2013
DOI: 10.1002/pat.3228
|View full text |Cite
|
Sign up to set email alerts
|

Phenylboronate-diol crosslinked polymer/SWCNT hybrid gels with reversible sol-gel transition

Abstract: This work demonstrates the successful incorporation of functionalized single‐walled carbon nanotubes (f‐SWCNTs) into the phenylboronate‐diol crosslinked polymer gel to create a hybrid system with reversible sol–gel transition. The phenylboronic acid‐containing and diol‐containing polymers were first separately prepared by the reversible addition–fragmentation chain transfer polymerization. Covalent functionalization of single‐walled carbon nanotubes (SWCNTs) with an azide‐derivatized, diol‐containing polymer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
(51 reference statements)
0
13
1
Order By: Relevance
“…Unsurprisingly, increasing the concentration of insulin in the solution used for loading leads to greater LCs but lower EEs. The loading observed in this work is higher than that in other reports: Guo et al 34 reported an LC of ~10% and EE of ~60%, while Li et al 39 obtained an LC of ~13%. …”
Section: Insulin Loading and Releasecontrasting
confidence: 76%
See 1 more Smart Citation
“…Unsurprisingly, increasing the concentration of insulin in the solution used for loading leads to greater LCs but lower EEs. The loading observed in this work is higher than that in other reports: Guo et al 34 reported an LC of ~10% and EE of ~60%, while Li et al 39 obtained an LC of ~13%. …”
Section: Insulin Loading and Releasecontrasting
confidence: 76%
“…The mass loss at 313-360°C corresponds to the thermal decomposition of pendent sugar residues. 39,40 The last stage of mass loss is the thermal degradation of the backbone, which occurs at a lower temperature for PAD-5-1 than for p(AAPBA). These observations agree closely with the literature.…”
Section: Abbreviationsmentioning
confidence: 99%
“…These self-healing hydrogels can be used as adsorbents in the removal of Rhodamine 6G (Rh6G) from water. Carbon nanotubes and graphene oxide were also used in the preparation of self-healing nanocomposites hydrogels in addition to clay and gold nanoparticles [77][78]. Graphene oxide (GO) based self-healing nanocomposite hydrogels were prepared for biomedical applications [77].…”
Section: Self-healing Polymer Nanocomposite Hydrogelsmentioning
confidence: 99%
“…It was concluded that this methodology provides a new approach to prepare smart materials with multifunctional applications. Self-healing nanocomposite gels were prepared employing phenylboronate-diol crosslinked polymers that were incorporated with functionalized singlewalled carbon nanotubes (f-SWCNTs) [78]. Crosslinking of the mixture of f-SWCNTs and diol-containing polymer with phenylboronic acid-containing polymers was carried out to synthesize SWCNT/ gel nanocomposites.…”
Section: Self-healing Polymer Nanocomposite Hydrogelsmentioning
confidence: 99%
“…A great number of studies have demonstrated that a small amount of carbon-based NPs, such as CNTs or graphene, in the polymer matrix can markedly change its mechanical, electrical and thermal properties [ 87 , 88 , 89 , 90 ]. However, the key problem of the practical use of CNTs is their poor dispersibility in water, organic solvents and polymer matrix [ 87 , 88 , 89 , 90 , 95 , 96 ]. Generally, some pretreatments, such as functionalization with strong acid or surface modification with surfactants, polymers or proteins, are needed to improve the dispersion of CNTs [ 25 ].…”
Section: Composites Of Hydrogels and Nanoparticlesmentioning
confidence: 99%